Effect of Potent Ethyl Acetate Fraction of Stereospermum suaveolens Extract in Streptozotocin-Induced Diabetic Rats. (19th April 2012) - Balasubramanian, T.; Chatterjee, Tapan Kumar; Senthilkumar, G. P.; Mani, Tamizh
Abstract : To evaluate the antihyperglycemic effect of ethyl acetate fraction of ethanol extract of Stereospermum suaveolens in streptozotocin-(STZ-) induced diabetic rats by acute and subacute models. In this paper, various fractions of ethanol extract of Stereospermum suaveolens were prepared and their effects on blood glucose levels in STZ-induced diabetic rats were studied after a single oral administration (200?mg/kg). Administration of the ethyl acetate fraction at 200?mg/kg once daily for 14 days to STZ-induced diabetic rats was also carried out. The parameters such as the fasting blood glucose, hepatic glycogen content, and pancreatic antioxidant levels were monitored. In the acute study, the ethyl acetate fraction is the most potent in reducing the fasting serum glucose levels of the STZ-induced diabetic rats. The 14-day repeated oral administration of the ethyl acetate fraction significantly reduced the fasting blood glucose and pancreatic TBARS level and significantly increased the liver glycogen, pancreatic superoxide dismutase, and catalase activities as well as reduced glutathione levels. The histopathological studies during the subacute treatment have been shown to ameliorate the STZ-induced histological damage of pancreas. This paper concludes that the ethyl acetate fraction from ethanol extract of Stereospermum suaveolens possesses potent antihyperglycemic and antioxidant properties, thereby substantiating the use of plant in the indigenous system of medicine.